Freud’s letters during the great war: between horror and condescendence (2014)
Freud’s correspondence duringWorld War I, also known as theGreat War, reveals the effects thewar had on him, as well as hiswagers, inconsistencies, and contradictions.In those letters, Freudshows himself as a subject dividedbetween horror and condescendence.His encounter with theconflict makes it possible to clarifythe logic of war and its subjectiveimplications, on the basis of his wartimeenthusiasm, his confrontationwith the spectacle of destruction,inhibition of activity, shame, separationfrom his loved ones, thesudden end of the war, and thesuspension of judgment in viewof the return of “his” combatants.